The processes of democratisation and trust in political institutions in Slovenia - Haček, Miro (Annales. Series historia et sociologia, 2014)
After the collapse of the non-democratic regime in the early 1990s, public opinion surveys became important factor in the process of democratic decision-making. Authors are analysing the results of public opinion surveys, which bring together data on the attitude of the general public towards democracy, (dis)satisfaction with the political situation and (dis)satisfaction with most important political institutions; special emphasis is given to the general public's (dis)trust toward the judiciary. Based on the data obtained authors allocate Slovenia's position compared to other established European democracies as well as post-communist countries from Central and Eastern Europe (CEE) on the scale of the relationship of the dimensions of societal trust in political power.
Keywords: democracy; Democratization; demokracija; Demokratizacija; Political institutions; politics; Politične institucije; politika; Slovenia; Slovenija; Trust; Zaupanje